2019
DOI: 10.1111/apt.15529
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of the specialised blood fibrosis tests FibroMeterV2G and Enhanced Liver Fibrosis score in patients with non‐alcoholic fatty liver disease from tertiary care centres

Abstract: Summary Background The Enhanced Liver Fibrosis score (ELF) and the FibroMeterV2G are two specialized blood fibrosis tests which include direct markers of liver fibrosis. They have been shown to be more accurate than the simple blood fibrosis tests FIB4 and the non‐alcoholic fatty liver disease (NAFLD) fibrosis score (NFS). Aims To directly compare the accuracies of ELF and FibroMeterV2G for the non‐invasive diagnosis of liver fibrosis in NAFLD. Methods Four hundred and seventeen patients with biopsy‐proven NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 56 publications
0
57
0
3
Order By: Relevance
“…Experts propose as the gold standard for detection and grading of the hepatic steatosis, using the intrahepatic TG measurement with the magnetic resonance imaging derived proton density fat fraction (MRI-PDFF) [128,129]. Subjects with intermediate or high risk of severe fibrosis may benefit from FibroMeter that performs better than the simple FIB4 and NFS tests, and can measure the hepatic extracellular matrix components [130]. Also, Ampuero et al [131] developed and validated recently the Hepamet fibrosis scoring system, a noninvasive scoring test with 97.2% specificity and 74% sensitivity that uses clinical and laboratory information from NAFLD subjects and can identify fibrosis stage with better accuracy than NFS and FIB-4.…”
Section: Screening and Assessmentmentioning
confidence: 99%
“…Experts propose as the gold standard for detection and grading of the hepatic steatosis, using the intrahepatic TG measurement with the magnetic resonance imaging derived proton density fat fraction (MRI-PDFF) [128,129]. Subjects with intermediate or high risk of severe fibrosis may benefit from FibroMeter that performs better than the simple FIB4 and NFS tests, and can measure the hepatic extracellular matrix components [130]. Also, Ampuero et al [131] developed and validated recently the Hepamet fibrosis scoring system, a noninvasive scoring test with 97.2% specificity and 74% sensitivity that uses clinical and laboratory information from NAFLD subjects and can identify fibrosis stage with better accuracy than NFS and FIB-4.…”
Section: Screening and Assessmentmentioning
confidence: 99%
“…+++++AUC ≥0.90, ++++AUC 0.85–0.89, +++AUC 0.80–0.84, ++AUC 0.75–0.79, +AUC <0.75 (Harrell’s c index substituted for AUC for prognostic category).*Accuracy for determining advanced (bridging) fibrosis abstracted from meta-analyses where available7 9 12 118 or from large cohorts of chronic liver disease patients 26 59 74 119–123†Proportion of cases falling within an indeterminate range for the prediction of advanced fibrosis 6 38 72 119 120 124–127‡AUC for significant (F2-4) fibrosis.ALD, alcoholic liver disease; ALT, alanine aminotransferase; Apo-A1, apolipoprotein-A1; APRI, AST-Platelet Ratio Index; AST, aspartate aminotransferase; AUC, area under the curve; BMI, body mass index; CHB, Chronic hepatitis B; CHC, chronic hepatitis C; HA, hyaluranic acid; IFG, impaired fasting glucose; α2-M, α2-macroglobulin; NA, not applicable; NAFLD, non-alcoholic fatty liver disease; PNPIII, procollagen N-terminal peptide III; PSC, primary sclerosing cholangitis; PTI, prothrombin index; TIMP-1, tissue inhibitor of matrix metalloproteinase-1.…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…†Proportion of cases falling within an indeterminate range for the prediction of advanced fibrosis 6 38 72 119 120 124–127…”
Section: Blood-based Biomarkersmentioning
confidence: 99%
“…24 Other studies have confirmed the accuracy of the ELF score in the assessment of hepatic fibrosis in PLWH and in those with NAFLD. [25][26][27][28] Assuming the SD of the ELF score is 1.12, with 20 patients in each group for the analysis, a difference in ELF of 1 point can be estimated with a 95% CI from 0.6 to 1.4. Assuming an attrition rate of 33%, a target of 30 individuals will be recruited per group.…”
Section: Post-trial Carementioning
confidence: 99%